Study of diabetes mellitus among patients with sickle cell disease - Bariha, Prafulla Kumar; Prusty, Biswaranjan; Mohapatra, Manoj Kumar (International Journal of Research in Medical Sciences, 2020)
Background: Type 2 diabetes mellitus (T2DM) occurs when impaired insulin effectiveness is accompanied by decreased insulin production by β cells. With 366 million people diagnosed in 2011 and a trend of increasing prevalence worldwide (Lyssenko and Laakso 2013), diabetes is one of the major threats to human health. Objectives of the study were to assess the occurrence of diabetes mellitus in sickle cell disease (SCD) patients and to study glycemic status of patients with SCD and clinical presentation. Methods: An observational study was done at department of general medicine and sickle cell clinic and molecular biology laboratory, Veer Surendra Sai institute of medical science and research, Burla between November 2014 to October 2016. All recorded data analyzed through standard statistical methods including standard diagram and groups and finding were discussed in detail to draw appropriate conclusion, through standard statistical methods including standard diagrams. Results: The study was taken on 137 cases of SCD patients admitted at VIMSAR, Burla. Sex distribution of SCD patient with male (68.81%) and female (31.38%) clinical feature of SCD patients shows VOC (vaso occlusive crisis) was the most common presentation for hospital admission followed by fever, anemia, jaundice, AVN (avascular necrosis), osteomyelitis, dactylitis. The most of SCD are having normoglycemic with most of diabetes mellitus are in control group. Glycemic status in SCD cases and controls with 6.57% cases of SCD, 13.14% of controls are hyperglycemic. Conclusions: The majority of patients in this SCD patients were between the age group 15-20 years. The occurrence of diabetes mellitus in SCD patients is low in compare to control population. Showing impairment of glucose tolerance in SCD but low presence of diabetes mellitus. presence of lower life span of RBC, hypermetabolic state and low body mass index in SCD patients.